Analyzing the effects of fluctuating methanol feed concentration in active-type direct methanol fuel cell (DMFC) systems. (27th April 2015) - Gwak, Geonhui; Lee, Kise; Ferekh, Saad; Lee, Suwon; Ju, Hyunchul
Abstract In active-type direct methanol fuel cell (DMFC) systems, the methanol feed concentration inevitably fluctuates for various reasons, such as inaccuracy in the methanol sensors or the complexity of injecting additional methanol and/or water into the anode fuel recirculation loop. In this study, we use theoretical computations to examine the effects of fluctuating methanol feed concentration on the time-dependent behavior and resultant cell performance of DMFCs. Using a one-dimensional (1-D) two-phase transient thermal DMFC model, we conducted 1-D transient simulations under various DMFC operating conditions with different anode/cathode stoichiometries, cell operating temperatures, and cathode inlet humidification conditions. The simulation results clearly address the influences of these operating parameters on the evolution of cell voltage, cell temperature, methanol crossover, and overall efficiency, highlighting that fluctuation in methanol concentration on the DMFC performance induces fluctuations in these key profiles. Finally, we propose an optimum strategy to mitigate the influence of the fluctuating methanol feed concentration, i.e., purposely fluctuating the anode or cathode stoichiometry. The simulation results clearly show that when a fluctuating methanol feed concentration is present, a constant cell voltage of approximately 340 mV was successfully maintained by fluctuating the cathode stoichiometry between 3.0 and 4.0.